Effects of urea topdressing time on yield, nitrogen utilization, and quality of mechanical direct-seeding hybrid indica rice under slow-mixed fertilizer base application - Sun, Yongjian; Xing, Mengwen; He, Ziting; Sun, Yuanyuan; Deng, Yuqian; Luo, Yongheng; Chen, Xuefang; Cao, Yun; Xiong, Wenbo; Huang, Xinghai; Deng, Pengxin; Luo, Min; et al. (Frontiers in Plant Science, 2024)
The use of controlled-release nitrogen (N) fertilizers has been shown to improve yield and N-use efficiency (NUE) in mechanical transplanted rice. However, the fertilizer requirements for mechanical direct-seeding rice differ from those for mechanical transplanted rice. The effects of controlled-release fertilizers on yield, NUE, and quality in mechanical direct-seeding rice are still unknown.Methods: Hybrid indica rice varieties Yixiangyou 2115 and Fyou 498 were used as test materials, and slow-mixed N fertilizer (120 kg hm -2 ) as a base (N 1 ), N 1 +urea-N (30 kg hm -2 ) once as a base (N 2 ), N 1 +urea-N (30 kg hm -2 ) topdressing at the tillering stage (N 3 ), N 1 +urea-N (30 kg hm -2 ) topdressing at the booting stage (N 4 ) four N fertilizer management to study their impact on the yield , NUE and quality of mechanical direct-seeding rice.Results and discussion: Compared with Yixiangyou 2115, Fyou 498 significantly increased photosynthetic potential, population growth rate, root vigor, and N transport rate by 3.34-23.88%. This increase further resulted in a significant improvement in the yield and NUE of urea-N topdressing by 1.73-5.95 kg kg -1 . However, Fyou 498 showed a significant decrease in the head rice rate and taste value by 3.34-7.67%. All varieties were treated with N 4 that significantly increase photosynthetic potential and population growth rate by 15.41-62.72%, reduce the decay rate of root vigor by 5.01-21.39%, promote the N transport amount in stem-sheaths (leaves) by 13.54-59.96%, and then significantly increase the yields by 4.45-20.98% and NUE of urea-N topdressing by 5.20-45.56 kg kg -1 . Moreover, the rice processing and taste values were optimized using this model. Correlation analysis revealed to achieve synergistic enhancement of high-yield, high-quality, and high-NUE in rice, it is crucial to focus on increasing photosynthetic potential, population growth rate, and promoting leaf N transport.Specifically, increasing the contribution rate of N transport in stem-sheaths is the most important. These findings offer an effective N management strategy for 4R nutrient stewardship (right source, right method, right rate and right timing) of mechanical direct-seeding hybrid indica rice.